Exploring Eight Grade Students’ Practices and Challenges in Telegram-Assisted Vocabulary Learning with Vocabulary Self-Collection Strategy (Vss): Action Research - Fatiha, Tsaniatul; Al-Baekani, Abdul Kodir; Hakim, Putri Kamalia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The objective of this study was to investigate eight grade studentsâ€™ practices and challenges in Telegeram-assisted Vocabulary Self-collection Strategy (VSS) in learning vocabulary.Â This research provides two research questions: (1) In what ways Telegram-assisted vocabulary self-collection strategy facilitates students in learning vocabulary? (2) What are the constraints of the students in learning vocabulary using Telegram-assisted vocabulary self-collection strategy?Â With a classroom action research (CAR) as the research design, the researcher employed a qualitative research methodology. Participants in this study were junior high school students in Indonesia's Bekasi region who were in their second year of eighth grade. In this study, the researcher's instruments included a VSS chart and a semi-structured interview. From this research, two key themes were found: (1) The studentsâ€™ engagement in learning vocabulary through Telegram-assisted Vocabulary Self-collection StrategyÂ and Â (2) The challenges of Telegram-assisted Vocabulary Self-collection Strategy in learning vocabulary.Â The results implies that Telegram-assisted VSS helps students to comprehend the text and improve their vocabulary knowledge.Â